Perioperative hypertensive response in a patient with implanted deep brain stimulation device: a case report - Ghaffar, Waleed Bin; Shahid, Muhammad Arham; Haq, Irfan Ul; Sohaib, Muhammad (Journal of the Pakistan Medical Association, 2023)
This case report features unique anaesthetic management of a patient with implanted deep brain stimulation (DBS) device undergoing abdominal surgery. It features the intraoperative measures taken for this patient for the implanted DBS. After turning off the DBS preoperatively, the patient showed an exaggerated sympathetic response which was very much resistant to medicines. It was unique to this patient that restarting the device alleviated refractory hypertension. The report also includes review of literature for anaesthetic management of patients with implanted DBS. Keywords: Deep brain stimulation, Dystonia, Hypertension, Hysterectomy.